Schlack, Tim, Corrall, Sheila, and Bracke, Paul. (Eds.) The social future of academic libraries: new perspectives on communities, networks, and engagement. London: Facet Publishing, 2022. - Maceviciute, Elena (Information Research an international electronic journal, 2022)
Schlack, Tim, Corrall, Sheila, and Bracke, Paul. (Eds.) The social future of academic libraries: new perspectives on communities, networks, and engagement. London: Facet Publishing, 2022.